Women and education (introduction to reflection about the beginnings of women’s learning) - Kiejzik, Lilianna (Filosofiya osvity. Philosophy of Education, 2014)
The article presents several issues that have been shown in the book Women in Philosophy. Philosophers about Women. Subjective Essays [Kobiety w filozofii. Filozofowie o kobietach. Eseje subiektywne] (Zielona Gora, 2012). Author pays attention to the problem of women’s education in the times of antiquity. She examines the main philosophical schools (for example, “Pythagorean Union”) and to the ideas of the most famous women (for example, Perictione, Sappho, Aristoclea, Hypatia). The article shows that in different records of ancient scholars we meet the names that are exectly the names of women. Although we have not many information, but it’s known that they were philosophers and scientists. Typically they were daughters of teachers of philosophy and mathematics or were taken to the Academy from the rich families. Author analyzes the sources of the history of women’s education, notes difficulties faced by women who wish to learn in the male, misogynistic environment of antiquity.